Computational mechanics evaluation of the structural capacity and raveling processes in permeable friction courses (PFC) (2020)
The main objectives of this work are to use 2D micromechanical computational models of Permeable Friction Courses (PFC) layers to identify the factors that determine the structural contribution of these layers, and to quantify the effect of several mechanical and environmental conditions on the degradation of PFCs. These mixtures are used as thin surface layers over conventional pavements, which are characterized for having an open gradation that results in high air void content (20%). This characteristic makes PFC highly permeable, which brings several safety and environmental benefits. However, the principal distress affecting the durability of PFCs is the loss of aggregates from the surface, a phenomenon known as raveling. Since the PFC microstructure geometry and the material properties are a fundamental parameter for the computational mechanical models, this work presents a novel methodology to generate random 2D PFC microstructures that efficiently represent the mechanical behavior of a 3D PFC. This methodology can be used to generate multiple random microstructures of any PFC mixture to conduct computational probabilistic and statistical studies of the functionality, durability and mechanical response of PFC mixtures under different field conditions. In addition, an experimental plan was proposed and developed to assess the combined effects of aging and moisture on the fracture properties of the asphalt mortar asphalt present at the stone-on-stone contacts within PFCs. The new methodology to generate 2D PFC microstructures and the material properties obtained from the experimental plan were used to evaluate the raveling susceptibility of PFC mixtures after several service years (6 years) using FE with realistic field operation conditions (e.g. different traffic and material degradation conditions). The results show that raveling within PFCs is promoted by aging, moisture damage, high traffic loads, braking and low transit speed